Modeling un-authorized land use sprawl with integrated remote sensing-GIS technique and cellular automata - Hj. Mohd. Noor, Norzailawati; Hashim, Mazlan (Springer Berlin Heidelberg, 2009)
We have used cellular automata integrated with GIS and remote sensing to analyze urban sprawl aiming at analyzing expansion of potential unauthorized land uses for residential, commercial and industrial based on spatial factor deriving from remote sensing high resolution data. The spatial factors considered are used as parameter to measure either land use in these expansion process develop as urban legal sprawl or sprawl with declined the development planned (un-authorized). Results of the study indicated that residential area is most probable risk to un-authorized land use sprawl, given set of spatial factors considering the vicinity of highway strip, land use segregation and leapfrog development.